Observational teamwork assessment for surgery: construct validation with expert versus novice raters. - Sevdalis, N; Lyons, M; Healey, A; Undre, S; Darzi, A; Vincent, C (2009)
OBJECTIVE: To test the construct validity of the Observational Teamwork Assessment for Surgery (OTAS) tool. SUMMARY BACKGROUND DATA: Poor teamwork in surgical teams has been implicated in adverse events to patients. The OTAS is a tool that assesses teamwork in real time for the entire surgical team. Existing empirical research on OTAS has yet to explore how expert versus novice tool users use the tool to assess teamwork in the operating room. METHODS: Data were collected in 12 elective procedures by an expert/expert (N = 6) and an expert/novice (N = 6) pair of raters. Five teamwork behaviors (communication, coordination, leadership, monitoring, and cooperation) were scored via observation pre, intra, and postoperatively by blind raters. RESULTS: Significant and sizeable correlations were obtained in 12 of 15 behaviors in the expert/expert pair, but only in 3 of 15 behaviors in the expert/novice pair. Significant differences in mean scores were obtained in 3 of 15 behaviors in the expert/expert pair, but in 11 of 15 behaviors in the expert/novice pair. Total OTAS scores exhibited strong correlations and no significant differences in ratings in the expert/expert pair. In the expert/novice pair no correlations were obtained and there were significant differences in mean scores. The overall size of inconsistency in the scoring was 2% for expert/expert versus 15% for expert/novice. CONCLUSIONS: OTAS exhibits adequate construct validity as assessed by consistency in the scoring by expert versus novices-ie, expert raters produce significantly more consistent scoring than novice raters. Further validation should assess the learning curve for novices in OTAS. Relationships between OTAS, measures of technical skill, and behavioral responses to surgical crises should also be quantified.